Apraxia profile differentiates behavioural variant frontotemporal from Alzheimer's dementia in mild disease stages. Issue 7 (23rd September 2014) - Johnen, Andreas; Tokaj, Amelie; Kirschner, Anne; Wiendl, Heinz; Lueg, Gero; Duning, Thomas; Lohmann, Hubertus
Abstract : Objective: Despite refined criteria for behavioural variant frontotemporal dementia (bvFTD), its differentiation from Alzheimer's dementia (AD) remains difficult at early clinical presentation. Apraxia is not considered as a supportive feature for the diagnosis of bvFTD, but for AD. However, only few studies have quantified praxis disturbances in mild disease stages and their specificity for AD compared with bvFTD remains indistinct. We explore apraxia in bvFTD and investigate the differential validity of apraxia screening tests to distinguish between AD, bvFTD and healthy controls (HC). Methods: We compared composite apraxia scores assessed with standardised neuropsychological screening tests as well as performance in praxis subdomains in patients who fulfil current clinical criteria for AD (N=20), bvFTD (N=20), and in HC (N=20). Results: Composite scores of apraxia screening tests provided high diagnostic accuracy for detecting mild stages of both neurodegenerative disorders compared with HC (sensitivity: 75–95%; specificity: 70–90%). Both patient groups showed pronounced impairments in limb praxis, especially in imitation of hand and finger postures (bvFTD: 71.7%; AD: 55.5%; HC: 86.7%) and pantomime of object use (bvFTD: 88.6%; AD: 81.4%; HC: 97.5%). Beyond that, patients with bvFTD displayed a unique profile of deficits for imitating face postures (bvFTD: 69%; AD: 88%; HC: 95.5%). Conclusions: Praxis disturbances are important but under-represented diagnostic features in mild stages of AD and bvFTD. Apraxia screening tests are easily applicable diagnostic tools, which may support clinical diagnoses of both neurodegenerative diseases. The analysis of individual apraxia profiles can effectively facilitate differential diagnosis of AD and bvFTD.